Low serum adiponectin level is associated with better physical health-related quality of life in chronic kidney disease - Ji Hye Kim (Nature Portfolio, 2021)
Abstract Hyperadiponectemia is paradoxically associated with renal disease progression and mortality in chronic kidney disease (CKD). Its association with health-related quality of life (HR-QOL) is unknown. This study aimed to verify the association between adiponectin and HR-QOL in Korean pre-dialysis CKD cohort. This cross-sectional study analyzed 1551 pre-dialysis CKD patients from KNOW-CKD (KoreaN Cohort Study for Outcome in Patients With Chronic Kidney Disease). Participants were categorized into three tertiles (T1–T3) according to adiponectin levels. HR-QOL was assessed using SF-36. High physical component summary (PCS) and mental component summary (MCS) were defined as highest quartile of each score. Multivariate logistic regression was used to analyze odds ratio (OR) and 95% confidence interval (CI) for high PCS and MCS. Prevalence of high PCS were 33.3%, 27.5%, and 17.0% and that of high MCS were 31.7%, 24.8%, and 21.3% for T1, T2, and T3 (both p for trend < 0.001). The adjusted OR [95% CI] of T1 and T2 in reference to T3 were 1.56 [1.09–2.23] and 1.19 [0.85–1.68] for high PCS and 1.19 [0.85–1.68] and 0.94 [0.68–1.29] for high MCS. Serum adiponectin level was inversely associated with physical HR-QOL in Korean pre-dialysis CKD patients. This relationship was independent of various cardiovascular risk factors.